2009
DOI: 10.2741/3303
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk signaling between mitochondrial Ca2+ and ROS

Abstract: Mitochondria are central to energy metabolism as the source of much of the cell’s ATP, as well as being a hub for cellular Ca2+ signaling. Mitochondrial Ca2+ is a positive effector of ATP synthesis, yet Ca2+ overload can lead to mitochondrial dysfunction and cell death. Moreover, Ca2+ uptake by mitochondria is involved in shaping cellular Ca2+ dynamics by regulating the concentrations of Ca2+ within microdomains between mitochondria and sarco/endoplasmic reticulum and plasma membrane Ca2+ transporters. Reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
287
0
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(315 citation statements)
references
References 251 publications
(257 reference statements)
13
287
0
15
Order By: Relevance
“…[124][125][126][127][128] ROS, through the regulation of hypoxia-inducible factor-1, are also important in O 2 sensing, 125 which is essential for maintaining normal O 2 homeostasis. In pathological conditions ROS are involved in inflammation, endothelial dysfunction, cell proliferation, migration and activation, extracellular matrix deposition, fibrosis, angiogenesis and vascular remodeling [129][130][131] ( Figure 3). …”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…[124][125][126][127][128] ROS, through the regulation of hypoxia-inducible factor-1, are also important in O 2 sensing, 125 which is essential for maintaining normal O 2 homeostasis. In pathological conditions ROS are involved in inflammation, endothelial dysfunction, cell proliferation, migration and activation, extracellular matrix deposition, fibrosis, angiogenesis and vascular remodeling [129][130][131] ( Figure 3). …”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…Changes in structure caused by oxidizing amino acid residues can change the activity of enzymes and ion transporters [30]. In the context of Ca 2+ signalling, redox state and ROS can stimulate, as well as inhibit Ca 2+ channels/pumps/exchangers, generally increasing Ca 2+ channel activity and inhibiting Ca 2+ pumps [31]. Precisely, ROS can directly, or indirectly through changes in cell redox homeostasis, oxidize redox-sensing thiol groups on the ryanodine receptors leading to channel stimulation.…”
Section: Signalling Roles Of Ca2+ and Rosmentioning
confidence: 99%
“…Inositol-1,4,5-triphosphate receptor channels are the primary Ca 2+ endoplasmic reticulum release channels, while sarco/endoplasmic reticulum and plasma membrane Ca 2+ ATPase are Ca 2+ re-uptake pumps. Furthermore, there is also an important plasma membrane Na + /Ca 2+ exchanger [31]. Its function is also modulated by oxidation.…”
Section: Signalling Roles Of Ca2+ and Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ROS/RNS are known to inhibit SERCA pumps and activate RyRs and IP 3 Rs. 14,15 Moderate levels of ROS/RNS modify Ca 2C oscillations Having established that massive ROS/RNS production by AlClPc photoactivation abolishes Ca 2C oscillations in MIN6 cells, we turned our attention to the effects of moderate ROS/ RNS levels. When photoactivating AlClPc with 10% LED intensity we observed that Ca 2C oscillations typically persisted, but with a modified profile.…”
mentioning
confidence: 99%